The Saanich Inlet Basin: A Natural Collector of Past Biological, Climatic, and Land-use Changes in Southwestern Canada Amplified by Results of ODP Leg 169S - Hobson, Lois; McQuoid, Mellisa; Turnicliffe, Verena (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary Saanich Inlet sediments contain one of the best-preserved biological records in the world. Frozen 1-2 m cores representing the last -130 years show a defore station-related increased input of terrestrial carbonto the basin, and cyclic variations inorganic carbon, diatoms, and fish remains that suggest a link to climate oscillations. Ocean Drilling Program cores from Leg 169S greatly extend the sediment record, to more than 10,000 years. Study or diatoms, carbon isotope ratios, and fish remains from these long ODP cores shows that the marine environment has been stable during the Holoccne. The long OOP cores also indicate that, beginning - 10,000 years B.P, Saanich Inlet basin rapidly assumed the broad-scale océano-graphie and biologic features seen today.